Analysis Of Factors Affecting Entrepreneurial Interest Among Management Students At STIE Bentara Persada, Batam - Sanga, Laurensius Dihe; Balun, Bernardus Somi (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This research aims to analyze the factors that influence students' entrepreneurial interest, focusing on entrepreneurial characteristics such as risk-taking courage, future orientation, and other contextual factors. The subjects of this study were 30 students from STIE Bentara Persada who participated in filling out a questionnaire related to entrepreneurial interest. The research findings show that 50% of students have leadership qualities; 36.7% of students have the courage to take risks, while 26.7% are future-oriented. Another factor found is that only 10% of students had an entrepreneurial spirit since childhood, while 33.3% feel capable of solving problems in business. This analysis also identifies that the environment, family support, and personal motivation play an important role in shaping students' entrepreneurial interest. Based on these results, it is concluded that balancing risk-taking courage and long-term orientation is key to encouraging entrepreneurial interest among students. There is a need for a more comprehensive entrepreneurial curriculum and increased access for students to gain practical experience in the business world.